Deterministic and cost-efficient change propagation analysis method for manufacturing process sequences. (May 2022) - Hermann, Lennard; Schütz, Maximilian; Coppers, Florian; Barth, Sebastian; Beckers, Alexander; Bergs, Thomas
Abstract: Manufacturing companies are increasingly confronted with the challenge of adapting components that are already established on the market. As a result, the existing manufacturing process sequences of the corresponding components must also be adapted. Due to the complex technical interdependencies of manufacturing process sequences, adaptations potentially cause change propagation. The change propagation must be considered to ensure the component's functionality and to enable the selection of the most economical adaptation for the established manufacturing process sequence to implement the required component change. As a contribution to considering change propagation in manufacturing process sequences, a methodology for the deterministic and cost-efficient change propagation analysis is introduced. A case study from medical technology is presented to supplement the explanation of the methodology's steps and to validate its applicability.